Penyuluhan Bahaya Kesehatan Akibat Gadget pada Anak dan Remaja di Wilayah Kelurahan Purwosari Kota Semarang - Ulfa Nurullita; Ratih Sari Wardani; Wulandari Meikawati; Riausah Anjani; Salsabela Ratna Duhita Alri; Avista Ayu Sulistyawati (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
A gadget is a small electronic device that has many functions, is designed with high technology, is practical to use, and is constantly undergoing updates. The use of gadgets is growing very quickly in all age groups, especially children and adolescents. The dangers of using gadgets can have an impact on the physical and psychological condition of the child. In 2019 and 2020 there was an increase in the number of children who had to be referred to psychiatric hospitals related to gadget addiction, soit was necessary to socialize about the dangers of gadgets in health. The purpose of this community service is to increase children's knowledge about the health hazards caused by the use of gadgets. Activities in the form of socializationabout gadgets and their dangers to health, with material in the form of understanding, types of gadgets, health impacts caused, and how to control and prevent them. The methods used are socialization, giving leaflets, and interactive discussions. The subjects targeted were children and adolescents assisted by the Nareswari Thematic Village, Purwosari Village, North Semarang District. The results of community service showed a higher knowledge score after socialization than before counseling.